Consumption behavior as a result of the pandemic in Bucaramanga and AMB - Prieto - Cuentas, Narcy Carolina; Theran - Barajas, Carmen Elisa (Universidad Francisco de Paula Santander, 2021)
This research is of a qualitative exploratory type and establishes changes in the consumption behavior of the inhabitants of Bucaramanga and its Metropolitan Area (AMB), as a result of the pandemic. It has been developed from the establishment of the partial panorama of with the Scopus tool in the year of the beginning of the spread of Covid-19 (2020), to date (April 2021); with the objective of establishing the trends and changes in consumption given in the period and their correlation with primary information obtained from the economically active population of Bucaramanga and its AMB. The main findings are an increase in the perception of consumption of products from the family basket by 45%, hygiene and cleaning products (53%) and a decrease in the consumption of liquors by 51%, pet products (34%), footwear and textiles (54%), household appliances (37%) and cosmetics (50%). Tourism and entertainment services show the greatest detriment with 77% and 78% respectively. Concluding that 66% of consumers have changed the way they buy their products.